Internet‐based information‐seeking behavior for transient ischemic attack. Issue 8 (18th August 2015) - Abedi, Vida; Mbaye, Marieme; Tsivgoulis, Georgios; Male, Shailesh; Goyal, Nitin; Alexandrov, Andrei V.; Zand, Ramin
Abstract : Background: In recent years, Internet became an increasingly important tool for accessing health information and is being used more frequently to promote public health. Aims and/or hypothesis: To use Google search data to explore information seeking behavior for transient ischemic attack. Methods: We selected two groups of keywords related to transient ischemic attack: 'Transient Ischemic Attack' and 'Mini Stroke'. We obtained all available online search data performed in the United States from the Google search engine for a 10‐year span – January 2004 to December 2013. The monthly and daily search data for the selected keywords were analyzed – using moving average – to explore the trends, peaks, and declining effects. Results: There were three significant concurrent peaks in the Google search data for the selected keywords. Each peak was directly associated with media coverage and news headlines related to the incident of transient ischemic attack in a public figure. Following each event, it took three‐ to seven‐days for the search trend to return to its respective average value. Furthermore, the trend was steady for 'Transient Ischemic Attack'; however, the search interest for the keyword 'Mini Stroke' shows a steady increase. The overall search interest for the selected keywords was significantly higher in the southeastern United States. Conclusions: Our study shows that changes in online search behavior can be associated with media coverage of key events (in our case transient ischemic attack) in public figures. These findings suggest that multimedia health promotion campaigns might be more effective, if increased promptly after similar media coverage.